Search for TeV emission from the region around PSR B1706-44 with the HESS experiment - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The region around PSR B1706 - 44 has been observed with the HESS imaging atmospheric Cherenkov telescopes in 2003. No evidence for gamma-ray emission in the TeV range was found at the pulsar position or at the radio arc which corresponds to the supernova remnant G343.1 - 2.3. The 99% confidence level flux upper limit at the pulsar position is F-ul( E > 350 GeV) = 1.4 x 10(-12) s(-1) cm(-2) assuming a power law (dN/dE proportional to E-Gamma) with photon index of Gamma = 2.5 and F-ul( E > 500 GeV) = 1.3 x 10(-12) s(-1) cm(-2) without an assumption on the spectral shape. The reported upper limits correspond to 8% of the flux from an earlier detection by the CANGAROO experiment.
CRIS-Team WoS Importer:2020-01-15